Facile synthesis of a flame retardant melamine phenylphosphate and its epoxy resin composites with simultaneously improved flame retardancy, smoke suppression and water resistance. Issue 68 (23rd November 2018) - Shi, Yilun; Wang, Zhengzhou; Zhou, Jian-an
Abstract : Melamine phenylphosphate (MPhP) was facilely synthesized and improved the flame retardancy, smoke suppression and water resistance of epoxy resin. Abstract : A flame retardant melamine phenylphosphate (MPhP) was facilely synthesized by the reaction of phenylphosphoric acid (PPA) and melamine (MEL), and was characterized by FTIR and NMR. Epoxy resin (EP) composites containing MPhP were prepared, and the effect of MPhP content on flame retardancy, smoke suppression, mechanical properties and thermal stability of the composites was investigated. It is observed that the LOI of the EP composite with 20 wt% MPhP (EP/MPhP20) is 26.5%, and the composite EP/MPhP20 reaches a UL 94 V-0 rating. Cone calorimeter test results show that the peak heat release rate, total heat release and total smoke release of EP/MPhP20 decrease by 51%, 34%, and 24%, respectively compared with those of pure EP. The flame retardancy of the EP/MPhP composites after the water treatment at 80 °C for 72 h is basically maintained, indicating that the composites have good water resistance. The mechanical strengths of the EP/MPhP composites decrease gradually with an increase in the MPhP content. Moreover, the thermal stability of the EP/MPhP composites was studied.